Mobilization, conservation and study of cultivated and wild potato genetic resources - S. D. Kiru; E. V. Rogozina (Вавиловский журнал генетики и селекции)
Nowadays, the world’s largest Potato Genebanks, including VIR Potato Genebank, hold about 98 thousand accessions of potato and its wild relatives. This gene pool, which has been accumulated for almost a century, represents a huge genetic diversity of tuber bearing species of the genus Solanum L., which has a great importance for basic and applied research in general, and for human food security. The genebanks of potato and other crops have three highly important tasks such as permanent replenishment of collection material, ensuring its preservation by various storage and maintaining methods, including seed and vegetative propagation, its all-round use in basic and applied research, as well as the improvement of the efficiency of agricultural production. Analysis of performance of the above tasks in genebanks and research institutes in most countries concerned with storage, study and use of potato germplasm, shows great results and achievements, both in terms of its biology and its improvement as a food crop. However, the above three ways to perform tasks still need to be improved in connection with progress made over past decades, in particular in the field of basic and applied sciences. In this paper, a brief analysis of the status of conservation, study and use of potato genetic resources and its wild relatives in the domestic and foreign breeding, as well as solutions of problems in these areas are provided. A great leap forward today is the use of molecular genetic methods for genotyping collection material in gene banks to identify and itemize collection samples, as well as for using this material in basic and applied research, including breeding programs. Coordination of efforts for the collection of wild species that are not in the collections or are represented by a small number of samples, as well as the exchange of material and information about it, will help expand genetic diversity in genebanks and knowledge of the biological features of the potato.